Ultraviolet Treatment of Titanium to Enhance Adhesion and Retention of Oral Mucosa Connective Tissue and Fibroblasts - Takayuki Ikeda (MDPI AG, 2021)
Peri-implantitis is an unsolved but critical problem with dental implants. It is postulated that creating a seal of gingival soft tissue around the implant neck is key to preventing peri-implantitis. The objective of this study was to determine the effect of UV surface treatment of titanium disks on the adhesion strength and retention time of oral connective tissues as well as on the adherence of mucosal fibroblasts. Titanium disks with a smooth machined surface were prepared and treated with UV light for 15 min. Keratinized mucosal tissue sections (3 × 3 mm) from rat palates were incubated for 24 h on the titanium disks. The adhered tissue sections were then mechanically detached by agitating the culture dishes. The tissue sections remained adherent for significantly longer (15.5 h) on the UV-treated disks than on the untreated control disks (7.5 h). A total of 94% of the tissue sections were adherent for 5 h or longer on the UV-treated disks, whereas only 50% of the sections remained on the control disks for 5 h. The adhesion strength of the tissue sections to the titanium disks, as measured by tensile testing, was six times greater after UV treatment. In the culture studies, mucosal fibroblasts extracted from rat palates were attached to titanium disks by incubating for 24, 48, or 96 h. The number of attached cells was consistently 15–30% greater on the UV-treated disks than on the control disks. The cells were then subjected to mechanical or chemical (trypsinization) detachment. After mechanical detachment, the residual cell rates on the UV-treated surfaces after 24 and 48 h of incubation were 35% and 25% higher, respectively, than those on the control surfaces. The remaining rate after chemical detachment was 74% on the control surface and 88% on the UV-treated surface for the cells cultured for 48 h. These trends were also confirmed in mouse embryonic fibroblasts, with an intense expression of vinculin, a focal adhesion protein, on the UV-treated disks even after detachment. The UV-treated titanium was superhydrophilic, whereas the control titanium was hydrophobic. X-ray photoelectron spectroscopy (XPS) chemical analysis revealed that the amount of carbon at the surface was significantly reduced after UV treatment, while the amount of TiOH molecules was increased. These ex vivo and in vitro results indicate that the UV treatment of titanium increases the adhesion and retention of oral mucosa connective tissue as a result of increased resistance of constituent fibroblasts against exogenous detachment, both mechanically and chemically, as well as UV-induced physicochemical changes of the titanium surface.